Reconceptualising Copyright Markets: Disseminative Competition as a Key Functional Dimension - Foong, Cheryl (Law School, University of New South Wales, 2021)
The notion of ‘markets’ occupies a prominent yet ambiguous position in copyright discourse. When the term is raised, the copyright owner’s market tends to be taken as its implicit meaning, perpetuating an assumption that the market needs to be protected solely to preserve incentives to create. This dominant narrative overshadows an important dimension of copyright markets – disseminative competition, which is characterised by rival disseminators competing for inputs (copyright content) and audiences (copyright consumers). With the aid of competition law principles, this article distinguishes competition for dissemination of content from competition for the creation of content. It underscores the importance of dissemination markets to a well-functioning copyright system and shows how certain copyright doctrines substantively impact on disseminative competition. In reframing contemporary understandings of copyright markets, this article highlights the biases in copyright infringement analysis that may favour incumbent content disseminators to the detriment of a vibrant and innovative digital economy.